Migration and Psychosis: Specificity and Burden on the Mental Health System in Italy. Issue 11 (November 2020) - di Giacomo, Ester; Giampieri, Emanuela D.; Pellicioli, Cristian; Rabboni, Massimo; Clerici, Massimo
Abstract : Abstract: In the last years, there has been a huge migratory flow to Italy. Migration is a risk factor for the development of psychopathology, especially psychosis and posttraumatic stress disorder. We aimed at investigating the burden and characteristics of psychotic features among immigrants in Lombardy, one of the most involved regions. A total of 7819 patients had at least one psychiatric appointment in 2013, 10.3% of them where immigrants. Patients from Africa showed a significant higher rate of psychosis, psychiatric onset, compulsory admissions, and number of professional appointments. Our result can confirm a cultural specificity of psychotic manifestations and their burden on the mental health system.